Review in the legislations of controlling pseudoephedrine in Malaysia / Siti Asiah Abdul Aziz - Abdul Aziz, Siti Asiah (2017)
A diversion of pseudoephedrine and its danger to society has been discussed in this research. The purpose of this research is to review the legislations of controlling pseudoephedrine in Malaysia which focus on the statutes namely the Poison Act 1952 (Act 366) and its regulations. The comparison with other jurisdictions such as Singapore, US and Australia (Victoria) has also been discussed in this research. This study had adapted a doctrinal approach and the semi structured interview that had been conducted during the period of research with the respondent from the Pharmacy Enforcement Division, Selangor State Health Department. As a result, this study have found that there are a differences of laws between other jurisdictions in controlling pseudoephedrine. The differences of laws can be considered as a weakness in Malaysian laws that should be strengthen to tighten up the existing regulatory restrictions. The area of manufacturing, sale, supply and disposal of pseudoephedrine is an area that diversion can potentially occur. Therefore, to improve the regulatory restrictions, there are several recommendations that had been suggested in this research including to come out with a specific regulations in controlling pseudoephedrine or precursors. Another recommendation propose is an amendment of Poison Act 1952 in order to adequately control pseudoephedrine.